2003
DOI: 10.1046/j.1432-1033.2003.03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Moult cycle‐related changes in biological activity of moult‐inhibiting hormone (MIH) and crustacean hyperglycaemic hormone (CHH) in the crab, Carcinus maenas

Abstract: The currently accepted model of moult control in crustaceans relies entirely on the hypothesis that moult-inhibiting hormone (MIH) and crustacean hyperglycaemic hormone (CHH) repress ecdysteroid synthesis of the target tissue (Y-organ) only during intermoult, and that changes in synthesis and/or release of these neurohormones are central to moult control. To further refine this model, we investigated the biological activities of these neuropeptides in the crab Carcinus maenas, at the target tissue, receptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 36 publications
3
105
0
Order By: Relevance
“…In recent years, a variety of other functions for these hormones have been established, involving (for example) inhibition of ecdysteroid (Webster and Keller, 1986;Chang et al, 1990;Chung and Webster, 2003;Chung and Webster, 2005), methyl farnesoate (Liu et al, 1997) and ovarian protein synthesis (Khayat et al, 1998;Avarre et al, 2001). A subject of topical interest is the involvement of CHH in ionoregulatory processes (Charmantier-Daures et al, 1994;Charmantier et al, 1999;Chung et al, 1999;Townsend et al, 2001;Serrano et al, 2003;Chung and Webster, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a variety of other functions for these hormones have been established, involving (for example) inhibition of ecdysteroid (Webster and Keller, 1986;Chang et al, 1990;Chung and Webster, 2003;Chung and Webster, 2005), methyl farnesoate (Liu et al, 1997) and ovarian protein synthesis (Khayat et al, 1998;Avarre et al, 2001). A subject of topical interest is the involvement of CHH in ionoregulatory processes (Charmantier-Daures et al, 1994;Charmantier et al, 1999;Chung et al, 1999;Townsend et al, 2001;Serrano et al, 2003;Chung and Webster, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As MIH transcript levels remain constant over the molt cycle, MIH synthesis and secretion are regulated by post-transcriptional mechanisms (Chung and Webster, 2003) (our unpublished observations). NO inhibits neuropeptide release in the hippocampus, bovine chromaffin cells, basal forebrain and nucleus accumbens in the mammalian brain (Sequeira et al, 1997;Schwarz et al, 1998;Philippu and Prast, 2001).…”
Section: Research Articlementioning
confidence: 74%
“…mRNA levels of MIH and crustacean hyperglycemic hormone (CHH) in the ESG remain unchanged throughout the molt cycle in Carcinus maenas, indicating that MIH and CHH are regulated post-transcriptionally (Chung and Webster, 2003) (our unpublished observations). The MIH neurons in the XO/SG complex are under serotonergic control (Rudolph and Spaziani, 1991) and neuropeptide release is triggered by entry of Ca 2+ (Cooke, 1985).…”
Section: Introductionmentioning
confidence: 74%
“…However, the study with the crab Carcinus maenas L., 1758 demonstrated that the sensitivity of Y-organ itself to MIH is a more important factor than levels of MIH (Chung & Webster 2003). This was also supported by a study with prawn Macrobrachium rosenbergii De Man, 1879, where female eyestalk ablation resulted in shortening of the reproduction molting period but levels of ecdysteroid (as well as vitellogenin) did not substantially vary during molting stages (Okumura & Aida 2001).…”
Section: Neuroendocrine Control Of Reproductionmentioning
confidence: 93%
“…Consequently, regulation of the sensitivity of Y-organ to MIH seems to have an important role. In fact, it has been shown that sensitivity of Y-organ to MIH significantly dropped in the premolt stage, and it was restored again during later molt and postmolt stages, but the factor that modulates the perceptivity of Y-organ has not been described (Chung & Webster 2003). Factors such as alterations in cellular second messengers (cAMP), modulations of steroidogenic enzymes or cholesterol uptake into Y-organ were suggested to be involved (Spaziani et al 1999).…”
Section: Role Of Classical Endocrine Glands In Reproductionmentioning
confidence: 99%